Community Organizing and the Detroit Water Struggle: Report from the Front Lines. Issue 2 (4th May 2018) - Rall, Ann
ABSTRACT: At this moment in history, both the need for macro social work approaches and interest in macro social practice among social workers are growing. One macro approach that is particularly well-suited to confronting current political and economic conditions is grassroots community organizing. Some authors have suggested that most successful efforts at community organizing are those which can link the lived experiences of grassroots community members to larger movements for social justice. The struggle for access to affordable water in Detroit is a prime example of such an effort. In 2014, indignation at the announcement that the city would be shutting off the water of all those who could not afford to pay their water bills, combined with resistance to the imposition of emergency management on the city, galvanized a movement that brought together a wide variety of community members, activists, and organizers. As a participant-observer in this struggle, I conducted videotaped interviews with 15 organizers and activists concerning their views on the successes and challenges they have witnessed and the crucial "next steps" for community activists in Detroit. This article reports on these interviews and examines the lessons for community organizers that emerged from them.